Rethinking chapter 3 of the basic conditions of Employment Act 75 of 1997: towards an 𝘜𝘣𝘶𝘯𝘵𝘶-𝘣𝘢𝘴𝘦𝘥 theory - Vatsha, Khanyisile (University of the Free State, 2024)
The Basic Conditions of Employment Act 75 of 1997 (BCEA), gives effect to section 23 of the Constitution, which provides for the right to fair labour practices.¹ Since the enactment of the BCEA and other labour legislations such as the Labour Relations Act 66 of 1995 and the Employment Equity Act 55 of 1998, South African employees and employers enjoy a variety of labour rights. The BCEA regulates and establishes basic conditions of employment and has the duty to comply with the International Labour Organization.² Chapter 2 of the Act regulates working time including ordinary work hours, overtime work, compressed working week, averaging of hours, determination of hours of work by the minister, meal intervals, daily and weekly rest period, pay for work on Sundays, night work and public holidays.³ In the context of this research, the regulation for the minimum and maximum working hours and conditions emphasize how the Act aims at protecting workers’ rights. ‏ Chapter 3 of the BCEA regulates ‘leave entitlements’‏⁴ To summarise the Chapter, section 20 provides for annual leave,⁵ section 21 regulates pay for annual leave,⁶ section 22 regulates sick leave whilst section 23 deals with proof of incapacity,⁷ section 24 regulates application to occupational accidents or diseases,⁸ section 25 regulates maternity leave, parental leave, adoption leave as well as commissioning parental leave⁹ section 26 deals with the protection of employees before and after childbirth, and lastly¹º section 27 regulates family responsibility leave.¹¹ This research focuses on Chapter 3 of the BCEA, with the aim of navigating whether Chapter 3 does not deviate from the main objectives of the BCEA as per the preamble of the Act and the stipulations of section 23(1) of the Constitution which provides for the right to fair labour practices.¹² This research draws motivation from various sections of the Constitution that support the approach followed by the paper. For example, section 9(3) of the Constitution prohibits unfair discrimination on one or more of the mentioned grounds, which include gender, pregnancy, belief, race, language, birth and others,¹³ and section 39(1) of the Constitution, which charges courts or tribunals to consider international law when interpreting the Bill of Rights and allows them to also consider foreign law.¹⁴ The research is also motivated by novel cases such as 𝘝𝘢𝘯 𝘞𝘺𝘬 𝘢𝘯𝘥 𝘖𝘵𝘩𝘦𝘳𝘴 𝘷 𝘔𝘪𝘯𝘪𝘴𝘵𝘦𝘳 𝘰𝘧 𝘌𝘮𝘱𝘭𝘰𝘺𝘮𝘦𝘯𝘵 𝘢𝘯𝘥 𝘓𝘢𝘣𝘰𝘶𝘳, 𝘔𝘢𝘩𝘭𝘢𝘯𝘨𝘶 𝘷 𝘚𝘢𝘮𝘢𝘯𝘤𝘰𝘳 𝘊𝘩𝘳𝘰𝘮𝘦 𝘓𝘵𝘥,¹⁵ 𝘛𝘰𝘺𝘰𝘵𝘢 𝘚𝘰𝘶𝘵𝘩 𝘈𝘧𝘳𝘪𝘤𝘢 𝘔𝘰𝘵𝘰𝘳𝘴 (𝘗𝘛𝘠) 𝘓𝘵𝘥 𝘷 𝘕𝘜𝘔𝘚𝘈 𝘰𝘣𝘰 𝘕𝘫𝘪𝘭𝘰 𝘢𝘯𝘥 𝘖𝘵𝘩𝘦𝘳𝘴,¹⁶ 𝘔𝘢𝘯𝘺𝘦𝘵𝘴𝘢 𝘷 𝘕𝘦𝘸 𝘒𝘭𝘦𝘪𝘯𝘧𝘰𝘯𝘵𝘦𝘪𝘯 𝘎𝘰𝘭𝘥 𝘔𝘪𝘯𝘦 (𝘱𝘵𝘺) 𝘓𝘵𝘥,¹⁷ which have recently contributed to the debate on the content and interpretation of Chapter 3 of the BCEA. These and other cases will be referenced to draw an inference of the possible deviation by Chapter 3 of the BCEA. This research finds that although the preamble of the BCEA provides for wide and generous conditions of employment to protect workers, Chapter 3 of the BCEA falls short of fulfilling the objectives of the Act. This is because through recent interpretations of Chapter 3 of the BCEA in case law, there seems to be a disconnect in relation to the letter of the law, the purpose of the law and the application of the law. Chapter 3 fails to adequately bring to life the protections envisaged by the preamble and the objectives of the Act. This then brings to the fore the question of whether Chapter 3 of the BCEA is effective in fulfilling the objectives of the Act or if there is a need for an alternative theory and approach. Upon navigating the lacuna and shortcomings from Chapter 3 stipulations, an alternative theory is investigated. In this light, the research looks at the possibility of adopting an Ubuntu-based theory in approaching leave entitlements, founded on the values of generosity, compassion, kindness, humanity, respect, and dignity will be analysed as a feasible alternative approach.¹⁸